Factors associated with the implementation of nursing documentation in a psychiatric hospital - Iswa Ramadhansyah Purnomo; Mudatsir Mudatsir; Marthoenis Marthoenis (Golestan University of Medical Sciences, 2024)
Background: Nurses constitute a significant portion of the health care workforce, playing a crucial role in enhancing the quality of hospital services, particularly in the context of nursing documentation to ensure the precise recording of patient information in accordance with established standards. This study examines the factors associated with implementing nursing documentation in a psychiatric hospital. Methods: This cross-sectional study was conducted in June 2023 in a psychiatric hospital in Indonesia. A convenience sampling method was employed to recruit 144 nurses working in the hospital. Data collection methods encompassed supervision questionnaires, Unified Motive Scales (UMS), and observation sheets used for recording nursing care activities. Data analysis involved the chi-square test and multiple logistic regression. Data analysis was performed with a significance level set at 0.05 and a CI of 95%, utilizing STATA 13. Results: We found significant associations between nursing documentation and supervision techniques (p = 0.01), need for power (p = 0.001), and need for affiliation (p = 0.002). Notably, the need for power emerged as the most influential factor in nursing documentation (odds ratio [OR] = 8.46; 95% CI, 3.53-20.28). Conclusion: These findings underscore the importance of supervision techniques, power needs, and affiliated needs in the context of nursing documentation. The statistically significant associations between these factors emphasize their role in ensuring accurate and comprehensive record-keeping within health care settings. Particularly noteworthy is the substantial influence of the need for power, with a high OR, suggesting that addressing power dynamics may be an essential strategy for improving nursing care documentation practices.